Consciência sintática no plano textual: um estudo realizado com alunos dos anos iniciais do Ensino Fundamental I - Santos, Thaís Vargas dos; Pereira, Vera Wannmacher (Linguarum Arena, 2020)
This article has as theme the syntactic awareness of children of the 3rd, 4th and 5th years of Elementary School I. The main objective is to expose the bases, processes and results of a study developed to examine the level of syntactic awareness (use and awareness in use) of 40 students from these school years, based on an instrument built for this purpose, focusing, in this article, the textual plan. It is theoretically supported on Psycholinguistics and its relations with Syntax, with regard to studies in the use and awareness in the use of ten selected syntactic contents. Methodologically, the syntactic awareness instrument, with focus on these topics, uses four operative categories, being presented in this article only the judgment task on the textual level. The results achieved are: a Syntactic awareness instrument for the investigation of the 3rd, 4th and 5th grade of Elementary School, focusing, in this article, the textual plan; the performance of students in the use of syntactic cases and in the syntactic awareness of their use evidenced by the application of the constructed instrument. The results obtained point, based on the statistical treatment, to the existing correlations with regard to syntactic content, use and awareness in use and school years.